Comparative Study of Antibiotic Resistance in Clinical and Environmental Bacterial Isolates in the Pakistani Population - Sadia Rashid, Faisal Latif, Sana Sabir, Muhammad Zeeshan Alam Khan, Muhammad Bilal, Hafiz Muhammad Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Antibiotic resistance poses a critical threat to global health, particularly in Pakistan where unregulated antibiotic use, limited healthcare resources, and complex human–animal–environment interactions accelerate the spread of resistance. Aims and Objectives: This study aimed to compare antibiotic resistance profiles between clinical and environmental bacterial isolates. Methodology: A total of N=50 non-duplicate isolates were collected from January 2022 to December 2022, including 25 clinical isolates from tertiary care hospitals and 25 environmental isolates from surface waters, wastewater treatment plant effluents, and agricultural sites. Standard identification was made using standard microbiological techniques, such as colony morphology, Gram staining and biochemical tests, with a subsequent polymerase chain reaction (PCR) confirmation for specific pathogens. Kirby-Bauer disc diffusion method was used to determine Antibiotic susceptibility and resistance patterns were analysed using descriptive statistics and chi square test. Results: Clinical isolates demonstrated more significant resistance rates than environmental isolates. Resistance to ampicillin occurred in 80% of clinical isolates as opposed to 48% of environmental isolates, and multidrug resistance was seen in 56% of clinical isolates and 20% of environmental isolates. For ceftriaxone, ciprofloxacin, and tetracycline, similar patterns were observed, and differences were significant (p < 0.05). Conclusion: These findings underscore a striking disparity between clinical and environmental isolates in terms of antibiotic resistance and underscore the urgency for the implementation of measures to improve antibiotic stewardship, comprehensive surveillance, and integrated intervention measures to combat antimicrobial resistance in Pakistan. Our findings offer data that may help to direct future policy and research and improve public health outcomes. Keywords: Antibiotic resistance, clinical isolates, environmental isolates, multidrug resistance, Pakistan, surveillance, stewardship.